Aesthetic Dimensions in Nadine Gordimer's Post-apartheid Short Fiction: The Case of Loot and Beethoven Was One-sixteenth Black. Issue 1 (2nd January 2017) - Tiwari, Kusha
Abstract : This article examines Nadine Gordimer's post-apartheid short story collections, Loot and Other Stories and Beethoven Was One-sixteenth Black in the light of her artistic capability, expression and innovation. In her non-fiction writings including her Nobel Prize speech, Gordimer talks of the Chekhovian influence on her creative sensibility. This Chekhovian influence is notably visible in her post-apartheid short fiction, in which Gordimer, like Chekhov, disavows moral, structural and thematic finality in the narrative. The stories in these collections prompt debates around the role of a socially motivated writer in contemporary global networks.